PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PERANGKAT DESA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI - Amin Wahyudi, Sumarsih & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2009)
ABSTRACT This research aim to to analysis the leadership influence Lead the Countryside to performance of countryside peripheral District of Kalijambe of Sub-Province Sragen, analysis leadership influence Lead the Countryside, cultural organization which moderate motivate the job to performance of countryside peripheral District of Kalijambe of Sub-Province Sragen Population research Countryside peripheral Kalijambe of Sub-Province Sragen amounting to 153 people. Sum up the sampel in this research counted 55 people. technique of Intake sampel use the proporsional random sampling. Result analyse the regression that organization culture which dimoderating motivate the have an effect on to performance of countryside peripheral District of Kalijambe of Sub-Province Sragen, from result this is can be said that the quality of leadership lead countryside District of Kalijambe of Sub-Province Sragen pickaback performance of countryside peripheral can improve the quality of and service to better society progressively To challenge global leader require to push the existence of countryside peripheral to powered human resource the interest development, education and practice also often study to compare in other area to increase resource of countryside peripheral so that can improve the quality of job and service to society. Keywords : organization culture, performance, leadership, motivastion